CANDI BENTAR MONUMEN RELIGIUS HINDU (Suatu Kajian Historis Teologis) - Dharmawan, I Gusti; Wijayanti, Ni Putu Sri; Wiguna Murti, I Wayan Indra (Widya Katambung, 2024)
Hindus construct holy places (pura) to symbolize Mount Mahameru, the highest mountain in Indonesia. These temples represent Mount Kailasa (Kailas), the abode of Bhatara Shiva (the Supreme God). Each temple typically features a "Candi Bentar," which serves as the entrance to the outer courtyard leading to the inner courtyard. Over time, influenced by Hindu art and culture, Candi Bentar has expanded beyond sacred sites to also appear in traditional Balinese homes, hotels, and even as boundary markers for Pakraman villages. This trend raises the question of how Candi Bentar differs when situated in temples compared to its presence in residential and commercial settings in Bali. The aim of this research is to address the issues arising from the proliferation of Candi Bentar, not only in temples but also in residential homes, hotels, and as village boundaries. This field research seeks to uncover the meanings attributed to Candi Bentar by the community in various contexts. The study utilizes symbolic theory to explore its functions and semiotics to understand the meanings of Candi Bentar in temples, traditional Balinese housing, hotels, and village boundaries. Data collection involves observation, interviews, and reviews of documents and literature. The research is presented in a qualitative, interpretive, and descriptive format. The findings reveal that Candi Bentar shares similarities in function and meaning—historically, theologically, and philosophically—across sacred places, traditional Balinese housing, hotels, and village boundaries. This shared meaning aligns with the development concepts outlined in Asta Kosala-Kosali and Asta Bumi, derived from Silpasastra by Bhagawan Wiswakarma. These concepts describe traditional Balinese architecture as embodying sacred values and integrating the microcosm with the macrocosm. Each traditional Balinese building serves as a medium for connecting humans with the divine, with each other, and with the natural environment.